Arnold Beckman, with two unidentified men, receiving an award from the Scientific Apparatus Makers Association (Arnold Beckman at award dinners, 1974)
Arnold Beckman, with two unidentified men, receiving the Scientific Apparatus Makers Association 1974 award.
Keywords: Beckman, Arnold O.; Scientific Apparatus Makers Association; Award presentations